Effects of antacids, ferrous sulfate, and ranitidine on absorption of DR-3355 in humans. - Shiba, K (1992)
This study examined the effects of widely used antacids (aluminum hydroxide, magnesium oxide, and calcium carbonate), ferrous sulfate, and ranitidine on the absorption of a fluorinated quinolone, (-)-(S)-9-fluoro-3-methyl-10-(4-methyl-1-piperazinyl)-7-oxo-2,3-dihydro- 7H- pyrido-[1,2,3,-de][1,4]benzoxazine-6-carboxylic acid hemihydrate (DR-3355), in healthy male volunteers enrolled in three separate randomized crossover studies. Study 1 used 100-mg doses of DR-3355 and concurrent doses of aluminum hydroxide (1 g) or magnesium oxide (500 mg), while study 2 used DR-3355 (100 mg) and concurrent ferrous sulfate (160 mg) or calcium carbonate (1 g). Study 3 used DR-3355 (100 mg) and concurrent ranitidine (150 mg). Each study included control doses of DR-3355 (100 mg) alone. When aluminum hydroxide, ferrous sulfate, and magnesium oxide were coadministered with DR-3355, the relative bioavailability of DR-3355 was decreased to 56, 81, and 78%, respectively, of that for DR-3355 (100 mg) alone. Urinary excretion of DR-3355 was also significantly decreased by coadministration of these drugs. Thus, the magnitude of the decrease in the area under the concentration-time curve for DR-3355 varied among antacids, and the ranking of their inhibitory effects correlated with previously reported rankings of stability constants for chelate formation. DR-3355 bioavailability was not influenced by the concurrent administration of calcium carbonate and ranitidine, indicating that changes in gastric pH do not affect DR-3355 absorption.